2019
DOI: 10.3389/fendo.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

School Age Neurological and Cognitive Outcomes of Fetal Growth Retardation or Small for Gestational Age Birth Weight

Abstract: Children who were growth restricted in utero (FGR) and are born small for gestational age (SGA) may experience poorer long term neurological and cognitive outcomes. Those also born preterm may have particular difficulties. The objective of this paper was to review the literature on school age neurocognitive outcome for term and preterm children that was published in the last 15 years. Considering term born children first, there is evidence that these children are at higher risk for Cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 60 publications
(140 reference statements)
2
26
0
2
Order By: Relevance
“…The small range of gestational ages might have contributed to the lack of a significant relation. In literature both fetal growth restriction and birth weight are associated with poor neurodevelopment [31,32]. Our 2-year follow-up study found birth weight as a predictor of development in consensus with literature.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 89%
“…The small range of gestational ages might have contributed to the lack of a significant relation. In literature both fetal growth restriction and birth weight are associated with poor neurodevelopment [31,32]. Our 2-year follow-up study found birth weight as a predictor of development in consensus with literature.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 89%
“…Prematurity and small-for-gestational age (SGA) are consistently associated with poor postnatal growth and development [55, 56]. Premature infants are vulnerable to prolonged hospitalisation and are at greater risk for neonatal infection and sepsis [57].…”
Section: Pathogenesis—universal Pathways Versus Hiv-specific Pathways?mentioning
confidence: 99%
“…In addition to this series, no significant difference in incidence of behavioral problems, asthma, eczema, or problems with speech were found between 29 exposed children, with a mean follow-up of 54 months, and 114 non-exposed children [ 12 ]. Of note, available data are still too limited to make robust conclusions and highlights the need for continuous follow-up, especially as children born SGA seems to be at risk for neurological dysfunction [ 47 ].…”
Section: Discussionmentioning
confidence: 99%